Analisis faktor pemanfaatan pelayanan Rumah Sakit Jiwa: Systematic literature review - Nabilah Salsabilah; Zahroh Shaluhiyah; Syamsulhuda Budi Mustofa (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: Mental disorders are illnesses that have an impact on mood, behavior, thinking, or a combination of the three. In Indonesia, there are 236 million people who suffer from mental illnesses, with moderate mental disorders accounting for 6 percent of the population and severe mental illnesses for 0.17 percent of the population, 14.3 percent of whom are shackled. Up to 61.86 percent of individuals with mental illnesses lack access to basic medical care. This is due to the fact that Indonesia's access to mental health care has not been equal, high-quality, or cost-effective.Purpose: Provide an overview of the factors that influence the use of mental hospital services.Method: The Google Scholar, Scient Direct, Spinger, and Proquest databases were used to conduct article searches and were done between 2017 and 2022. The keywords